Clinical symptom improvement and lipidomic signatures in overweight/obese PCOS treated by lifestyle and acupuncture intervention - Zhang, Haolin; Tian, Wenmin; Li, Dong; Chen, Yang; Ye, Yang; Huo, Zejun; Shi, Li; Fukuzawa, Ii; Yang, Shuhan; Yang, Yang; Zhang, Hua; Zeng, Lin; et al. (Frontiers in Medicine, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is interrelated with obesity. Lifestyle intervention, mainly focusing on weight loss, has emerged as promising strategies to improve fertility outcomes in women with obesity. Acupuncture can aid in weight loss through metabolic regulation. However, evaluating the effectiveness of lifestyle and acupuncture in improving symptoms of polycystic ovary syndrome is still lacking.ResultsThis study aims to evaluate the efficacy of long-term lifestyle and acupuncture treatment on PCOS and elucidate the lipidomic features of these interventions in patients with overweight/obese PCOS, and identify potential therapeutic targets. Thirty-one women with PCOS and twenty-eight age and BMI matched controls were recruited. The participants with PCOS were randomly assigned to either lifestyle and acupuncture intervention group (A&L) or Lifestyle and sham acupuncture group (SA&L) for 4 months. The patients were followed up for an additional 4 months. Clinical indices indicating hyperandrogenism, homeostasis and quality of life was collected to evaluate the effectiveness of treatments. Comprehensive lipidomic analyses by utilizing mass spectrometry were conducted to profile the lipidomic signatures of participants with PCOS before and after treatment. After the A&L intervention, the BMI of participants with PCOS was significantly reduced. Assessments of insulin resistance (HbA1c, HOMA-IR, ISI), hyperandrogenism (SHBG, FAI), physical activity, and β-endorphin showed significant improvement. Lipidomic analysis revealed a panel of lipid species that effectively distinguished participants with PCOS from those without PCOS (AUC = 0.9747). Serum 18:0 Lyso PI, involved in intracellular insulin signaling pathways, was specifically associated with the A&L regimen. The co-regulation of 18:0 Lyso PI and 16:0 SM (d18:1/16:0) were associated with the A&L regimen.Conclusion18:0 Lyso PI may be a potential biomarker for A&L therapy in PCOS patients.